Pengembangan Modul Berbasis Inquiry Terintegrasi Islam pada Materi Sistem Pencernaan untuk Meningkatkan Nilai-Nilai Islami Siswa Kelas XI SMA Muhammadiyah 4 Kartasura - Nila Masnuri Yunita; Maridi Maridi; Baskoro Adi Prayitno (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2019)
This research aimed to: (1) Development of integrated Science-Islamic Inquiry Biology module to improve the religiosity behavior of high school class XI students. (2) Knowing the feasibility of Islamic Science-based Biology Inquiry modules in Islamic Schools. (3) Improving students' critical thinking after using an integrated Science-Islamic Inquiry Biology module in class XI SMA. This of research is research and development using a modification of the Four-D Model (4-D Model) which consists of 4 stages, namely: define, design, develop, and spread ( disseminate). Qualitative data were obtained from observations and questionnaires, while quantitative data were obtained from the results of assessment of module validation, questionnaire assessment on product trials (limited trials and extensive trials), operational trials, and learning outcomes. Data analysis with quantitative descriptive techniques. The results of this study indicate that: (1) the validation of religious material and biology material experts is in very good criteria (88,50%); (2) validation of design experts in good criteria (90,00%); (3) validation of langue experts in good criteria (93,75%); and (4) validation of learning media experts in good criteria (95,31%). Assessment studies of biology teachers are in very helpful criteria (88,01%); (5) individual testing in good criteria (90,71%). So it can be concluded that the Integrated Science-Islamic Digestive System-Based Module Class XI SMA is suitable to be used as a support for digestive system learning in an Islamic school environment.